(untitled) (Journal of Statistics on Health Decision, 2021)
Background: Adverse drug reactions (ADRs) are a public health problem. Tapentadol is a novel opioid analgesic with a dual mode of action that was approved for acute and chronic pain. This drug has been associated with several ADRs, particularly involving Nervous System Disorders, Psychiatric Disorders, Gastrointestinal Disorders, and General Disorders and Administration Site Condition. Objective: Since published studies on tapentadol-associated ADRs are limited, the major aim of this study was to characterise ADRs’ reports related to tapentadol included in EudraVigilance (EV). Methods: The data analysed was retrieved from EV - the European database of suspected ADR reports, between January 1st, 2017 and October 17th, 2019. The ADR reports in which tapentadol was not the only reported drug of interest were excluded. We selected 865 cases from a total of 1467 reports identified. Results: Within the selected ADR reports, the majority referred to cases involving adults. A predominance of female ADR reports (64.05%) was also observed. The five most frequent ADRs reported were nausea (9.36%), dizziness (9.25%), vomiting (4.86%), confusional state (4.62%) and headache (4.51%). Eight cases of serotonin syndrome were reported. Most patients recovered completely. Fatal outcomes were shown to be rare (2.66%). Conclusions: Pharmacovigilance databases are important tools to evaluate the safety and efficacy profiles of drugs, thus improving patients’ safety and quality of life. Despite an overall safety profile, the prescription of tapentadol still demands for caution and ongoing monitoring, in order to decrease its known and potential associated ADRs.